Enhanced liquid biofuel production from crude palm oil over synthesized NiMoW-ZSM-5/MCM-41 catalyst. Issue 2 (17th January 2018) - Subsadsana, Maliwan; Sansuk, Sira; Ruangviriyachai, Chalerm
ABSTRACT: Micro-mesoporous ZSM-5/MCM-41 composites were prepared and then loaded with varied contents of NiMoW by the wet impregnation method. The hydrocracking conversion of crude palm oil to liquid biofuels with the prepared catalysts was carried out in a batch reactor at 400°C for 2 h. ZSM-5/MCM-41 composite exhibited 51.00% conversion with a yield of 9.23% gasoline, 20.60% kerosene, and 21.17% diesel. Upon loading of NiMoW, the catalysts exhibited an improved conversion (≥ 62.60%) and a reduced formation of coke, which resulted from combined properties of ZSM-5 with MCM-41 and the presence of dispersed NiMoW. The contents of impregnated metals also affected the performance of catalysts. Using ANOVA analysis ( p < 0.05), we found that 8:8:8 wt.% NiMoW-ZSM-5/MCM-41 catalyst was suitable for the production of biofuels, when considering the efficiency and cost-effectiveness.